PERAN MADRASAH DALAM MENGHADAPI ERA GLOBALISASI DAN BUDAYA - Moh. Toriqul Chaer (MUADDIB Jurnal Kependidikan dan Keislaman, 2016)
The development of the madrasa in the context of modern it is quite interesting if it is linked with the phenomenon of globalization which brings significant changes to systems and madrasah curriculum which previously was the result of the development of the educational system individually and pretty loaded with Islamic education. Recent development shows that the madrasa has been doing adaptations with the demands of globalization, which became a milestone for the formation of "modern" madrasah with an image in contrast to the madrasa. In this context, the madrasa seems to not see globalization as a thing to be feared but should be faced.